Is There a Need for a More Expansive Use of Ethics and Values in Reflecting on the Use of Animals in Scientific Research? - Mark W. Fisher (Animals, 2014)
Although reflecting a long tradition of moral reflection that the use of animals is acceptable as long as it is humane, the tension between causing harm to animals in research and the benefits to humans can nevertheless be troubling. Utilitarian arguments that appeal to the value of those practices in sustaining and enhancing human lives, and rights-based arguments which seek to constrain them, can be inadequate. Reflecting a more engaging, inclusive and sophisticated understanding of human activity, justification for animal use could be expanded to reflect the fullness and richness of ethical thinking. This might see more explicit inclusion of perspectives borne of virtues, caring, experiences, and respect for the essence of the animal, and different ways of understanding and knowing animals, values drawn from the middle ground of commonly acceptable human-animal relationships. Such values, already clearly evident in research, could be more widely integrated into arguments justifying animal use. A more expansive approach would not only reflect reality and acknowledge that costs and benefits are shared more widely, but it might result in more equitable, effective and humane science. It might also serve to reduce some of the tension long evident in the relationship between humans and animals.